PERANCANGAN ANTENA MIKROSTRIP ARRAY BERBENTUK MAWAR PATCH DENGAN PENCATUAN FEEDLINE PADA FREKUENSI WLAN 2.4 GHz DAN 5.2 GHz - Mohammad Hamdani (Institut Sains dan Teknologi Nasional, 2020)
This research discusses the design of the microstrip array antenna with the rosette patch model that works on WLAN 2.4 GHz and 5.2 GHz frequencies which are used for WIFI networks. This microstrip antenna is made using a feedline feed or direct feed with a directional radiation pattern. The initial design used Ansoft HFSS v.13. Software, then fabricated the Microstrip Antenna using a PCB with a single layer FR4 type, and consisted of a patch, substrate, and groundplane. This antenna has dimensions of 94 mm in length and 63.3 mm in width. The measurement results in Laboratorium obtained VSWR 1.6, return loss -12.817, and 31.357 impedance, at a frequency of 2.4 GHz. While at a frequency of 5.2 GHz the VSWR value is 1.292, return loss is -18,210, and impedance is 46.417.